Constructing Sacred Meaning through Music, Language, and Imagery : A Semiotic Analysis of Qolbi fi al-Madinah - Hidayatullah, Achmad Diny (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
Islamic devotional music has become a transnational medium of spiritual expression, resonating across cultures and generations through emotional, lyrical, and symbolic depth. This study aims to analyze the semiotic structures embedded in the song Qolbi fi al-Madinah by Maher Zain, applying Louis Hjelmslev's metasemiotic framework. This qualitative research uses a descriptive-interpretative method, drawing data from the song's lyrics, melody, and official music video. The primary data sources are audiovisual materials published by Awakening Music, and the analysis involves segmenting expression and content into four levels: expression form, expression substance, content form, and content substance. Results show that the melody forms a progressive spiritual journey, while the lyrics encode themes of longing, submission, and devotion using ritualistic language. The music video further enhances the narrative through symbolic visuals of journeying toward Madinah, culminating in emotional and theological resolution. The study concludes that Qolbi fi al-Madinah constructs a multidimensional sign system where music, language, and imagery converge to produce mediated religious meaning. These findings contribute to the study of Islamic popular culture, digital da'wah, and semiotic-based religious communication.